Prevalência e fatores associados à dor em professores de educação física em academias de ginástica da cidade do Salvador-BA - Gonçalves, Ciro Alexandre Mercês (2012)
Physical Education professionals are usually exposed to excessive physical workloads that evolve into painful symptomatology and muscle and bone disorders that originate from the work-related exercises. Purposo: The goal of this study was to investigate the prevalence and factors associated with pain painful symptomatology in teachers in gymnastics academies. An analytical transversal cut study was performed involving 163 gymnastics teachers working in the main gyms in the city of Salvador-BA. For evaluation of pain, validated versions in Portuguese of the McGill Protocol and the Wisconsin Pain Inventory were used. For obtain results of descriptive statistical analysis of the collected data was performed, followed by TStudent, and Pearson and Spearman correlation tests to verify possible correlations between the presence of pain and other variables which were considered independent. Finally, for the identification of potential risk factors associated with pain, a binary logistic regression analysis was performed. For all statistical analysis, we cnsidered p< 0.05. Results: The painful symptoms was reported by 88.3% of the subjects surveyed. High pain levels were observed in 63.8% of the interviewed professionals, where the intensity varied from moderate to severe. Pain in the lumbar region was present in 55.2% of subjects. Positive correlations were found between the level of pain intensity and the variables related with the workload activity and daily life of the teachers in almost all body joints analyzed. Some factors had been verified associates to the painful sintomatologia as the age of the professionals, the daily hours load of labor work, and the lack of interval of rest between the lessons. Conclusions: We found a high prevalence in gym teachers working in the city of Salvador-BA, which interfered in various daily activities of their home and professional lives. The most affected region was the lumbar region, followed by the knees, neck, shoulders, ankles, hands, hips, feet, elbows and forearms. The factors associated with development of painful symptomatology were the age of the professionals, daily hours of work and the lack of rest intervals between lessons. The high prevalence of pain in Physical Education teachers can be regarded as a serious occupational health problem, which would demand the urgent deployment of preventive intervention programs to minimize the impact of pain among these professionals